The Anti-Non-Small Cell Lung Cancer Cell Activity by a mTOR Kinase Inhibitor PQR620 - Zha, Jian-hua; Xia, Ying-chen; Ye, Chun-lin; Hu, Zhi; Zhang, Qin; Xiao, Han; Yu, Ben-tong; Xu, Wei-hua; Xu, Guo-qiu (Frontiers in Oncology, 2021)
In non-small-cell lung carcinoma (NSCLC), aberrant activation of mammalian target of rapamycin (mTOR) contributes to tumorigenesis and cancer progression. PQR620 is a novel and highly-potent mTOR kinase inhibitor. We here tested its potential activity in NSCLC cells. In primary human NSCLC cells and established cell lines (A549 and NCI-H1944), PQR620 inhibited cell growth, proliferation and cell cycle progression, as well as cell migration and invasion, while inducing significant apoptosis activation. PQR620 disrupted assembles of mTOR complex 1 (mTOR-Raptor) and mTOR complex 2 (mTOR-Rictor-Sin1), and blocked Akt, S6K1 and S6 phosphorylations in NSCLC cells. Restoring Akt-mTOR activation by a constitutively-active Akt1 (S473D) only partially inhibited PQR620-induced cytotoxicity in NSCLC cells. PQR620 was yet cytotoxic in Akt1/2-silenced NSCLC cells, supporting the existence of Akt-mTOR-independent mechanisms. Indeed, PQR620 induced sphingosine kinase 1 (SphK1) inhibition, ceramide production and oxidative stress in primary NSCLC cells. In vivo studies demonstrated that daily oral administration of a single dose of PQR620 potently inhibited primary NSCLC xenograft growth in severe combined immune deficient mice. In PQR620-treated xenograft tissues, Akt-mTOR inactivation, apoptosis induction, SphK1 inhibition and oxidative stress were detected. In conclusion, PQR620 exerted potent anti-NSCLC cell activity via mTOR-dependent and -independent mechanisms.